2004
DOI: 10.1056/nejmoa041125
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Surgical Cytoreduction for Advanced Ovarian Carcinoma

Abstract: For patients with advanced ovarian carcinoma in whom primary cytoreductive surgery was considered to be maximal, the addition of secondary cytoreductive surgery to postoperative chemotherapy with paclitaxel plus cisplatin does not improve progression-free survival or overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(168 citation statements)
references
References 28 publications
(24 reference statements)
7
150
0
11
Order By: Relevance
“…After screening the abstracts, assessing the full-text articles, and identifying additional records through the reference lists of selected articles, we included 5 RCTs [5][6][7][8][9], 3 meta-analyses, and 3 Cochrane reviews [10][11][12][13][14][15][16] in this review. Three RCTs compared NACT-IDS with chemotherapy only [5][6][7]. Two RCTs compared PDS with NACT-IDS [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…After screening the abstracts, assessing the full-text articles, and identifying additional records through the reference lists of selected articles, we included 5 RCTs [5][6][7][8][9], 3 meta-analyses, and 3 Cochrane reviews [10][11][12][13][14][15][16] in this review. Three RCTs compared NACT-IDS with chemotherapy only [5][6][7]. Two RCTs compared PDS with NACT-IDS [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Critics of secondary cytoreductive surgery counter that the same favorable prognostic factors that define ideal candidates for secondary cytoreductive surgery also characterize those patients who will experience extended postrecurrence survival with salvage chemotherapy alone. 34,35 These prognostic factors include the amount of residual disease after the procedure and the length of the disease-free interval. 9,10,12,[14][15][16][17][18][19][20][21][22][23][24][25][26]33 A number of studies have shown that patients who are left with no or minimal residual disease at the time of secondary cytoreductive surgery have a median survival that ranges from 38 months to 61 months compared with 4.5 months to 27 months for patients who undergo suboptimal cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the US GOG152 study and a small-scale British randomized controlled trial (RCT) (4,5) demonstrated no benefit in survival rates. Previous joint study efforts of the EORTC and National Cancer Institute of Canada identified that neoadjuvant chemotherapy is no less effective than standard first-line treatment (6,7). Nevertheless, in the present case neoadjuvant chemotherapy resulted in a favorable outcome.…”
Section: Discussionmentioning
confidence: 50%